Optimization of Electroless Plating Solution Parameter for Coating PETG Electrode with Copper using Design of Experiment (DOE) - Mun Kit, Fong; Abdul Haq, Reazul Haq; Singh, Yashvir; Abdul Ghafir, Mohammad Fahmi; Hassan, Mohd Fahrul; Syed Abu Bakar, Sharifah Adzila; Hoffmann, Jörg (semarak ilmu, 2025)
In the study, an attempt was made to electrolessly plate copper onto PETG plastics that aren't conductors. Three manipulating factors, i.e. volume of copper sulphate and sulphuric acid (A), volume of sulphuric acid (B), and mass of copper sulphate (C), were selected and carried out using Taguchi method with three levels to examine their interactions and effects on the responses, including plating thickness, and electrical resistance. The Design Expert 13 software creates a total of nine runs with a single centre point. Three days were spent submerging every electroplated sample part in a different bath solution concentration. The resistance of the metalized Polyethylene Terephthalate Glycol (PETG) component was measured in the meantime using a digital multi-meter. The Cu-deposited PETG was analysed and measured using scanning electron microscopy (SEM). The ideal situation was identified as having 10 possibilities for achieving the goal, based on interaction effects. According to the results of the experiment, run number 3 provides the ideal solution parameter for copper deposition metallization. For the lowest electrical resistance of 0.64 ohm and the highest plating thickness value of 211.49 m, these runs yield the best ideal results. Because each factor reacts to a response individually, the Analysis of Variance (ANOVA) demonstrates that there are little interactions between the factors and responses. The lowest electrical resistance and highest plating thickness values are obtained with the best chemical composition parameter choices